3.7 GHz repetition rate operated narrow-bandwidth picosecond pulsed Yb fiber amplifier with an all-fiber multiplier. (4th March 2016) - Wei, K H; Wen, R H; Guo, Y
Abstract: A high power picosecond pulsed Yb fiber amplifier with a pulse repetition rate of 3.7 GHz is experimentally demonstrated. The seed is a gain switched distributed Bragg reflection (DBR) structured laser diode (LD) with a pulse duration of 130 ps and a repetition rate of 460 MHz. The pulse repetition rate is increased to 3.7 GHz by introducing an all-fiber multiplier, which is composed of four 2  ×  2 structured fiber couplers. The multiplied pulse train is amplified to 81 W through two stage Yb fiber amplifiers.